Into the Deep: Teacher Reflections on the Development and Implementation of a Trial Religious Education Curriculum - Sultmann, William (Religious education, 2021)
The development and implementation of a trial Religious Education (RE) curriculum within a Catholic diocese of Australia was characterized by the scriptural metaphor “into the deep.” Commentary (5300 words) from teacher developers (n = 40) and implementers (n = 85) were analyzed using Interpretative Phenomenological Analysis. Findings indicate that the six RE Development Principles (REDP) were applied successfully to collaborative learning and teaching resources; and, significant to implementation were the application of creative pedagogies; a whole school approach to curriculum; and, teacher witness. Teachers affirmed the complementary support by school and system authority personnel, and within the local school community, professional learning was reinforced by teacher educators.